The missing voices in the perceptions of tourism: The neglect of expatriates. (April 2018) - Dutt, Christopher S.; Harvey, William S.; Shaw, Gareth
Abstract: The interconnected nature of tourism suggests it can offer alternative solutions and perspectives to a variety of situations which have hitherto been unexplored. This research reviews the extant literature pertinent to community tourism to explore potential gaps present, with a particular focus on the suggested impact upon expatriates. A number of gaps are uncovered, from both a tourism and expatriate perspective, including demographic discrepancies, lack of geographical representation, and the lack of temporal consideration, among others. These gaps offer future areas of analysis that can provide more insight into the possible role of tourism in improving expatriate adjustment, as well as areas of future community tourism analysis. Of specific note, the expatriate community has been by-and-large excluded from much of the analysis on perceptions of tourism, which holds significance given the increasing prominence of expatriates globally. Highlights: An evident literary gap is evident considering expatriates perceptions of tourism. A review of community tourism literature reveals a number of further areas of disagreement or gap. A better understanding of all residents' opinions can result in a more thorough understanding of perception of tourism. Inclusion of the whole host community can extend the usefulness of tourism, for example,  expatriate adjustment.